Domains in Kurdish Family-Related Proverbs (Raparin Journal of Humanities (RJH), 2025)
The current study investigates cognitive domains in selected Kurdish proverbs. A cognitive domain refers to a context of knowledge background that is essential for understanding meaning. Since Kurdish proverbs evoke many domains, Kurdish speakers usually struggle to understand their meanings and identify their facets. At this juncture, the question posed is: Is the meaning of a proverb based on the domain in which it is embedded? To that end, the study adopts Cognitive Semantics approach in analyzing the selected domains. One crucial assumption is that aspects of human cognition shape linguistic features. Applied to Kurdish, it is hypothesized that proverbs are not often meaningful without a larger framework, which consists of related concepts that represent experiences. As for data collection, the study relied on reliable sources such as Shekh Mohamad Khal (2007), Ali Marouf Sharazoori(2010), Hoshyar Noori Lak (2011), and Karim Sharaza (1983). As for data analysis, the study adopts a qualitative introspective approach. The study then aims to identify the role of cognitive domains in the semantic construction and configuration of proverbs. Precisely, the aim is to reduce the degree of misunderstanding and misinterpretation of the proverbs while they are being used. One interesting finding is that one cannot understand the meaning of a proverb without access to all the essential knowledge that relates to that proverb.